Polymorphous low-grade adenocarcinoma of parotid gland: A rare occurrence - Arathi N; Bage Atul (Wolters Kluwer Medknow Publications, 2009)
Polymorphous low-grade adenocarcinoma (PLGA) is a rare salivary gland malignant tumor of low aggressiveness, commonly occurring in minor salivary glands. Its occurrence in major salivary gland has been documented albeit rarely. The striking histological feature is architectural diversity combined with benign cytologic features. We report a case of PLGA arising from left parotid in a 25-year-old male patient. On light microscopy, varied patterns were seen .The cells were uniform with bland nuclei. Neural invasion was noted.